Association Between Productive Parameters and Intestinal Histomorphological Findings in Broilers Supplemented with Probiotics (Saccharomyces cerevisiae, Lactobacillus acidophilus and Bacillus subtilis) - Barros-Barrios,Owens J (Sociedad Chilena de Anatomía, 2021)
SUMMARY: This study evaluates the effect of probiotics Saccharomyces cerevisiae, Lactobacillus acidophilus and Bacillus subtilis on production parameters and intestinal histomorphology of broilers of 45 days of age. Eleven 45-day-old Ross 500 broilers were used and classified as control group (CG) (n = 5) or supplemented with probiotics group (n = 8). Histopathological evaluation of duodenum, ileum, and jejunum was performed. The area of the villi height, base and apex were evaluated as well as the size and number of crypts. In addition, mucus production was quantified in different portions of the small intestine. The villi present duodenum of broilers supplemented with probiotics had a greater area (p = 0.0127), a greater basal width (p = 0.0049) and a greater apical width (p = 0.0024), as well as a greater crypt area (p = 0.0189). Significantly higher levels of mucus were noted in the duodenum (p = 0.0480) and jejunum (p = 0.0480) of broilers supplemented with probiotics. We suggest that probiotic supplementation improve the intestinal nutrients absorption.